The Trope of Nature in Latin American Literature: Some Examples - Becky Boling (Studies in 20th & 21st Century Literature, 2006)
The article examines the trope of nature through selected texts from Latin American literature, from the writings of Christopher Columbus to more contemporary narratives such as those by Luis Sepúlveda and Mayra Montero. It focuses on the transition in the manner in which writers conceive of the "natural" world within their particular ideological contexts. From early manifestations of Utopian writing to texts extolling urbanization and development, the trope of nature undergoes several permutations which say a great deal about the ideological contexts of the writers and their conceptualization of the place of humans in the scheme of things. Late 20th century narratives mark a departure from earlier conceptualizations of nature. Nature is re-imagined under the urgency of ecology and globalization. In the writings of Sepúlveda, nature is both habitat and resource. In Un viejo que leía novelas de amor 'The Old Man Who Read Love Stories,' we have the reworking and resemanticization of the Sarmiento theme of civilization and barbarism whereas Montero in Tú, la oscuridad 'In the Palm of Darkness', documents in an apocalyptic style impending ecological disaster. The article surveys the trope of nature in order to underscore the current rise of an ecologically oriented literature.
Keywords: tropes; nature; Latin American Literature; trope of nature; Columbus; Sepúlveda; Mayra Montero; utopian writing; un viejo que leía novelas de amor; Sarmiento theme; civilization and barbarism; Tú la oscuridad; ecology